THE POLA KOMUNIKASI PENGAMEN JALANAN DI RUANG PUBLIK - Fauzan Ahdi Widyaputra (UKRI, 2026)
Street busking is part of the social dynamics of urban communities where public spaces are often utilized as arenas for interaction with the broader society. Busking activities at city intersections are not merely related to economic aspects but also involve complex communication practices between buskers and road users. This study aims to analyze communication patterns, symbolic meanings emerging from interactions between street buskers and road users in public spaces. This research employs a qualitative approach using the ethnography of communication method introduced by Dell Hymes. Data were collected through participant observation, in-depth interviews, and documentation of busking activities at urban intersections. Data analysis was conducted using the SPEAKING model, which includes setting, participants, ends, act sequence, key, instrumentalities, norms, and genre. The findings indicate that communication among street buskers at intersections demonstrates relatively structured interaction patterns despite the short duration of interaction. Buskers utilize both verbal and nonverbal communication strategies to attract attention and build empathy among road users. Furthermore, busking communication practices also carry symbolic meanings related to social representation and survival strategies in public spaces. This study concludes that busking activities can be understood as a form of survival communication practice that reflects individuals' adaptive capacity within urban social environments.